An exact solution for vibro-acoustic response of smart sandwich panels with MEE composite Layer. (15th April 2022) - Arunkumar, M.P.; Bhagat, Vinod; Geng, Qian; Li, Yueming; Pitchaimani, Jeyaraj
Abstract: To the best of our knowledge, this is the first endeavor to provide an exact solution for a vibro-acoustic response of Magneto-electro-elastic (MEE) composite plate and sandwich panels with MEE facings. The governing equation of motion is developed using Hamilton's principle considering the third-order shear deformation theory to account for transverse shear. Based on boundary conditions and the Maxwell equation, the variation of electric and magnetic potentials are adopted along the thickness of the MEE composite layer. Analysis of the vibro-acoustic response of sandwich panels which are extensively used in aerospace structures such as cellular, trapezoidal, triangular, and honeycomb are presented. Influences of electric and magnetic potential on the vibro-acoustic response are also presented for the different types of truss core and honeycomb core sandwich panels.